2022
DOI: 10.1159/000525863
|View full text |Cite
|
Sign up to set email alerts
|

Weighing the Risk Profile of Cervical Spine MRI in Evaluating Pediatric Cervical Spine Injuries

Abstract: Objective: Screening for cervical spine injury (CSI) after blunt trauma is common, but there remains varied practice patterns and clinical uncertainty regarding adequate radiographic evaluation. An oft-cited downside of MRI is the added risk compared to CT in the pediatric population; however, these specific risks have not yet been reported. This study examines the risks of cervical spine MRI in pediatric trauma patients in the context of what value MRI adds. Methods: Retrospective observational study of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…No MRI- or anesthesia-related adverse effects were reported in this study population, consistent with previously published observations of an excellent safety profile of MRI [ 7 ]. Our study shows that in a selected pediatric population, spinal MRI can usually be obtained without sedation or anesthesia for children aged 5 years or older (Supplementary Material 3).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No MRI- or anesthesia-related adverse effects were reported in this study population, consistent with previously published observations of an excellent safety profile of MRI [ 7 ]. Our study shows that in a selected pediatric population, spinal MRI can usually be obtained without sedation or anesthesia for children aged 5 years or older (Supplementary Material 3).…”
Section: Discussionsupporting
confidence: 91%
“…Another study by Henry et al [ 17 ] showed that STIR MRI had good sensitivity in pediatric cervical spine injuries and may be of clinical use in the clearance of the pediatric cervical spine. In a recent study by Lee et al [ 7 ], MRI was found to be 100% sensitive to unstable cervical injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is superior in visualizing the ligaments and comparable to CT in detecting bony injuries 9,10 . A recent retrospective analysis found MRI safe and 100% sensitive for unstable injuries in the pediatric population with suspected cervical spine trauma 11 . The most significant drawbacks of the MRI include the need for anesthesia in younger or restless children, higher cost per examination, and longer scanning time compared with CT or conventional radiographs.…”
mentioning
confidence: 99%
“… 9 , 10 A recent retrospective analysis found MRI safe and 100% sensitive for unstable injuries in the pediatric population with suspected cervical spine trauma. 11 The most significant drawbacks of the MRI include the need for anesthesia in younger or restless children, higher cost per examination, and longer scanning time compared with CT or conventional radiographs. Despite the higher sensitivity in ligamentous injuries, MRI does not necessarily yield additional value in the treatment of pediatric spinal trauma, 12 14 but its major advantage over CT is the lack of ionizing radiation.…”
mentioning
confidence: 99%